Elevated serum levels of IL-6 and CXCL9 in autoimmune retinopathy (AIR) patients - Detrick, Barbara (J Neuroimmunol, 2018)
Autoimmune retinopathy (AIR) is a rare immune-mediated retinopathy associated with circulating antiretinal antibodies (ARAs). Other prominent features of AIR include visual field deficits and photoreceptor dysfunction in the setting of progressive unexplained vision loss. The role of inflammation is poorly understood in AIR. Since cytokines play a central role in the initiation and development of inflammation, we evaluated the presence of proinflammatory cytokines and chemokines in AIR patient sera. We demonstrate that IL-6 and CXCL9 are both elevated in AIR patient sera. Moreover, the presence and concentration of these 2 molecules appear to correlate with AIR patient disease severity. This cytokine profile, IL-6 and CXCL9, has been described to participate in a variety of autoimmune and inflammatory diseases. Our study provides support for an activated inflammatory process in AIR and identifies possible mechanisms that can drive autoimmunity in this disease.